Pengaruh Program Kampus Mengajar Dalam Meningkatkan Kemampuan Membaca Dan Menulis SDN 32 Kota Bengkulu - Muhammad Rizki Minandar; Ade Tiara Yulinda; Tezar Arianto; Surya Ade Saputera (LPPI UMN AL WASHLIYAH, 2024)
This research aims to evaluate the Teaching Campus Program's influence in improving students' reading and writing skills at SDN 32 Bengkulu City. This program involves students as additional teachers in an effort to increase student literacy. The research methods used were direct observation, interviews, and analysis of reading and writing test results before and after the program. The research results show that the Teaching Campus Program has a significant positive impact in improving students' reading and writing abilities. The students showed increased learning motivation, self-confidence, and active participation in reading and writing activities. Apart from that, this program also received broad support from parents and school staff. Nonetheless, ongoing evaluation and adjustment of the program curriculum is necessary to ensure sustainability and continued improvement in student literacy. The Teaching Campus Program has great potential in improving the reading and writing skills of grade 1 and grade 2 students at SDN 32 Bengkulu City, provided that there is a need for continuous improvement and improvement through appropriate evaluation and adjustment.